2015
DOI: 10.1089/neu.2014.3535
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Frozen Plasma Resuscitation Provides Neuroprotection Compared to Normal Saline in a Large Animal Model of Traumatic Brain Injury and Polytrauma

Abstract: We have previously shown that early treatment with fresh frozen plasma (FFP) is neuroprotective in a swine model of hemorrhagic shock (HS) and traumatic brain injury (TBI). However, it remains unknown whether this strategy would be beneficial in a more clinical polytrauma model. Yorkshire swine (42-50 kg) were instrumented to measure hemodynamic parameters, brain oxygenation, and intracranial pressure (ICP) and subjected to computer-controlled TBI and multi-system trauma (rib fracture, soft-tissue damage, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…Neuroprotective effects of plasma in hemorrhagic shock and TBI are thought to be due to improved cerebral perfusion, decreased glutamate-mediated excitotoxicity, and reduction in mitochondrial dysfunction as demonstrated in animal models [28]. Plasma also reduced the size of brain lesions and swelling in multiple swine models of TBI and hemorrhagic shock [29,30]. It also incurs neuroprotection by providing higher brain oxygenation and cerebral perfusion profiles [30].…”
Section: Benefits Of Early Plasma Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroprotective effects of plasma in hemorrhagic shock and TBI are thought to be due to improved cerebral perfusion, decreased glutamate-mediated excitotoxicity, and reduction in mitochondrial dysfunction as demonstrated in animal models [28]. Plasma also reduced the size of brain lesions and swelling in multiple swine models of TBI and hemorrhagic shock [29,30]. It also incurs neuroprotection by providing higher brain oxygenation and cerebral perfusion profiles [30].…”
Section: Benefits Of Early Plasma Transfusionmentioning
confidence: 99%
“…Plasma also reduced the size of brain lesions and swelling in multiple swine models of TBI and hemorrhagic shock [29,30]. It also incurs neuroprotection by providing higher brain oxygenation and cerebral perfusion profiles [30]. In humans, a large retrospective cohort analysis showed that in the subgroup of patients with multifocal intracranial hemorrhage, early administration of plasma was associated with a survival benefit [31].…”
Section: Benefits Of Early Plasma Transfusionmentioning
confidence: 99%
“…Compared with other resuscitation fluids such as fresh frozen plasma (FFP) or colloids, normal saline resuscitation is furthermore associated with increased brain swelling (Jin, DeMoya, et al (2012;Imam et. al.…”
Section: Fluid Resuscitationmentioning
confidence: 99%
“…Our group and others have demonstrated that the choice of resuscitation fluid plays an important role in the severity of secondary brain injury. 21,53,54 Compared with crystalloids, artificial colloids (e.g. HEX), and fresh frozen plasma (FFP) have shown an increased ability to limit the extent of brain lesion size and swelling.…”
mentioning
confidence: 99%
“…HEX), and fresh frozen plasma (FFP) have shown an increased ability to limit the extent of brain lesion size and swelling. 21,53 While fluids do influence gene expression, such effects are likely minor compared with epigenetic modulators such as VPA, a known HDACI.…”
mentioning
confidence: 99%